Desenvolvimento de modelo murino de desnutrição baseado na dieta de crianças desnutridas e impacto na barreira morfofuncional intestinal - Ribeiro, Samilly Albuquerque (2022)
Child malnutrition has a complex pathology, associated with increased risk of mortality and susceptibility to infectious diseases, compromising the intestinal morphofunctional barrier, physical and neurocognitive development. This work aimed to formulate a new experimental diet based on the complementary diet of malnourished children from seven developing countries, to validate a new murine model of malnutrition, evaluating the impact of malnutrition on the intestinal morphofunctional epithelial barrier. The experimental diet (MAL-ED diet) was formulated considering the percentage difference in energy, macronutrients, fiber and zinc of children without malnutrition vs. with malnutrition (Z-score height for age < -2), with the composition of the standard diet for rodents (AIN-93M diet) being taken as a reference diet. Subsequently, male C57BL/6 mice (21 days of age) were submitted to the consumption of the control diet (AIN-93M) or MAL-ED diet for 28 days. Weight and feed were measured every day; body composition and length every seven days; lactulose/mannitol (LM), morphometry and albumin test on days 7 and 28; cotransport test in Ussing Chambers, analysis of intestinal transporters and tight junctions on day 7. The MAL-ED diet was shown to be moderately deficient in energy, proteins, lipids and zinc and with a moderate increase in carbohydrates and fiber in relation to the control diet. The consumption of this diet quickly reduced weight and weight gain, compromised energy reserves and caused growth failure in animals (p< 0.05) in a chronic period, without causing changes in albumin and edema levels (p> 0.05). In the intestinal morphofunctional barrier, the MAL-ED diet reduced the villi area in the duodenum and jejunum, caused an increase in the LM ratio, permeability, associated with an increase in FATCD/36 mRNA levels and a reduction in the basal potential difference (p< 0.05) in the acute period. In the chronic period, the MAL-ED diet increased intestinal area, small intestine length and paracellular permeability (p< 0.05). Thus, the new MAL-ED diet was able to cause malnutrition, compromise energy reserves and growth, without generating edema, causing a negative impact on the intestinal morphofunctional barrier in the acute period and an increase in the total intestinal area in the chronic period.